Defining Legal Boundaries of ‘Harm’ In Digital Expression in Indonesia and Thailand - Situmeang, Ampuan; Saefudin, Yusuf; Sohheng, Nipon; Rusdiana, Shelvi; Alhakim, Abdurrakhman (ADLIYA: Jurnal Hukum dan Kemanusiaan, 2025)
The enforcement of digital conduct provisions is currently gaining more relevance. Indonesia and Thailand, as two countries with diverse socio-cultural and religious backgrounds, continue to struggle with ensuring that online conduct was within safe boundaries. However, ongoing efforts to regulate this situation raised numerous questions regarding the balance between freedom of expression and societal sensitivities, particularly in relation to how ’harm’ was defined by individuals and the legal system. A normative legal study was conducted to analyze the relevant primary law sources from both countries and examined how ‘harm’ is defined by the Indonesian and Thailand legal system. The results showed that there was a significant disconnect between Indonesia and Thailand’s diverse societies and how the legal system tried to balance competing interests. Legal provisions and enforcement also showed a strong focus on socio-cultural preservation that may inadvertently limit digital discourse.